Competence as a Career Opportunity's Guarantor - Garleja, Rasma; Kangro, Ilmārs (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The aim of the research is to investigate the essence of the notion ”competence” and the differences in the usage of the career's terminology in semantic, methodological and pragmatic areas in academic theories of the second part of the 20 century; to work out evaluation criteria by comparing the succession of the notions capacity. The research is based on the Latvian and international sources of scientific literature – books, magazines, sources in digital form, and etc. A personality was investigated holistically ( Džarviss (Jarvis, 2010); Devis (Dove, 1976); Kross (Cross, 1981) ):Body (genetic, physical, biological; reflection, self-capacity);Mind (know-how – the cognitive skills being based on knowledge and competence; readiness for life activities; an attitude as a means of creativity; a system of evolution; imagination, confidence, sense).